Malnutrition in Hospitals: It Was, Is Now, and Must Not Remain a Problem! - Konturek, Peter C.; Herrmann, Hans J.; Schink, Kristin; Neurath, Markus; Zopf, Yurdagül (Medical Science Monitor, 2015)
BACKGROUND Malnutrition is an under-recognized problem in hospitalized patients. Despite systematic screening, the prevalence of malnutrition in the hospital did not decrease in the last few decades. The aim of our study was to evaluate the prevalence of malnutrition and to determine the explicit daily calorie intake of hospitalized patients, to identify the risk factors of developing malnutrition during hospitalization and the effect on the financial reimbursement according to the German DRG-system. MATERIAL AND METHODS 815 hospitalized patients were included in this study. The detection of malnutrition was based on the nutritional-risk-screening (NRS) and subjective-global-assessment (SGA) scores. A trained investigator recorded the daily calorie and fluid intake of each patient. Furthermore, clinical parameters, and the financial reimbursement were evaluated. RESULTS The prevalence of malnutrition was 53.6% according to the SGA and 44.6% according the NRS. During hospitalization, patients received on average 759.9±546.8 kcal/day. The prevalence of malnutrition was increased in patients with hepatic and gastrointestinal disease and with depression or dementia. The most important risk factors for malnutrition were bed rest and immobility (OR=5.88, 95% CI 2.25-15.4). In 84.5% of patient records, malnutrition was not correctly coded, leading to increased financial losses according to the DRG-system (94.908 Euros). CONCLUSIONS Hospitalized patients suffer from inadequate nutritional therapy and the risk for developing malnutrition rises during the hospital stay. The early screening of patients for malnutrition would not only improve management of nutritional therapy but also, with adequate coding, improve financial reimbursement according to the DRG-system.
EVALuna2:1991